Analisis Determinan Kejadian Anemia Ibu Hamil di Wilayah Kerja Kabupaten Ogan Komering Ilir Tahun 2025 - Eka Suryati; Faiza Yuniati; Sri Utari; Fika Minata Wathan (Jurnal Kesehatan Amanah, 2026)
Globally, anemia among pregnant women remains a major public health problem, with a prevalence of 41.8% in 2024 according to WHO data. In Indonesia, the incidence of anemia in pregnancy continues to increase, affecting both maternal and fetal health. Therefore, further analysis of the determinants influencing anemia among pregnant women is necessary. This study aimed to analyze risk factors associated with anemia and identify the dominant factor among pregnant women in the Working Area of Ogan Komering Ilir Regency in 2025. This research employed an analytical observational design with a cross-sectional approach, involving 110 pregnant women attending Muara Burnai, Kutaraya, and Rantau Durian Community Health Centers from July to August 2025, using Accidental Sampling technique. The results showed that most respondents were aged 20 years, had higher education, poor knowledge, income below the regional minimum wage, low family support, poor compliance with iron tablet consumption, and suboptimal ANC visit achievement. Significant associations were found between age, education, knowledge, family support, pregnancy interval, iron tablet adherence, and ANC visit achievement with anemia incidence, while occupation, income, and healthcare workers’ roles were not significantly related. The most dominant factor influencing anemia was ANC visit achievement. Improving ANC compliance and nutrition education should be prioritized to reduce the incidence of anemia among pregnant women.